Stigma in head and neck tuberculosis patients: Evaluation and analysis - Aytac, Ismail (Annals of Medical Research, 2021)
Aim: Stigma means wound, scar, degrading situation, labeling. In particular, patients with infectious diseases are exposed to stigma. The presence of stigma has a detrimental effect on the healing process, physical and mental problems of patients. For this reason, the study was performed to evaluate the stigma condition in head and neck tuberculosis cases.Materials and Methods: The research was carried out as descriptive with tuberculosis patients in the otorhinolaryngology clinic of a university hospital. The sample of the study consisted of 32 head and neck tuberculosis patients who are active in the treatment period. The data of the study were collected using the Patient Questionnaire and the Tuberculosis Patients Stigma Scale. The data obtained were evaluated by Pearson correlation analysis and t-test.Results: The average age of the patients was 39.5 ± 19.6 years, 65.6% were female, 31.3% were high school graduates, cervical region tuberculosis ranked first with 81.3%, and 34.4% of the patients were in denial regarding the disease. While 87.5% of patients had Bacillus Calmette-Guérin vaccine scar; 3.1% Acid-resistant bacilli test was found to be positive. The scale score average of the patients was found to be 99.8 ± 8.8. It was determined that the mean score of female patients was high, but there was no statistically significant difference between the mean scores of female and male patients (p> 0.05).Conclusion: In our study specifically for Head and Neck tuberculosis patients; The scale mean scores of all patients were found to be high. This shows that patients have high stigma levels. For this reason, it is recommended to inform the patient and family that head and neck tuberculosis patients can fully recover if they use their medication regularly by providing them with the necessary training about tuberculosis from the moment of diagnosis.
Keywords: Head and neck tuberculosis; stigma; tuberculosis; tuberculosis lymphadenitis